Development of digital literacy picture book knowledge training critical thinking in third grade students - Hasanah, Uswatun; Yasa, Arnelia Dwi; Kumala, Farida Nur; Aiman, Wan Muhammad (Jurnal Bidang Pendidikan Dasar, 2025)
Teachers need technology-based learning media to enhance student engagement in the learning process. The researcher found that some students had reading difficulties, resulting in poor understanding of the material and failure to achieve learning objectives. Therefore, digital media is needed as a solution to this problem. This study employed the ADDIE model. The research subjects were third-grade elementary school students in one of the schools in Malang. The research instruments were validated by media experts, language experts, and subject matter experts, and included questionnaires for student and teacher responses as well as tests. Data collection techniques included interviews and observations. This study was analyzed using both qualitative and quantitative approaches. The purpose of this research is to determine the feasibility, practicality, and effectiveness of a digital literacy-based picture book knowledge media. Based on the research findings, the media developed was declared to be highly feasible, highly practical, and effective.